Zambia's mining windfall tax - Olav Lundstøl; Jan Isaksen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
In 2008, the Government of Zambia reformed its mining tax regime for large-scale copper mines through a unilateral legislative change. The country went from having one of the lowest average effective tax rates and government take to be above the average. We focus on a particularly controversial element of the packet of changes: the windfall tax. We trace adjustments in the mining tax regimes since independence and calculate effective tax rates and the fiscal sharing between government and companies. Empirical evidence shows the 2008 mining tax regime as being both understandable and justifiable from an economic point of view, considering the nature of the state and the copper companies.
Keywords: Q00; Q01; Q28; Q32; Q38; 330; Zambia; mining; windfall tax; fiscal benefit sharing